2021
DOI: 10.1155/2021/2358060
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Blood and Urinary Concentrations of Metal Metabolites, Obesity, Hypertension, Type 2 Diabetes, and Dyslipidemia among US Adults: NHANES 1999–2016

Abstract: Background. Heavy metals are well known to be associated with cancer outcomes, but its association with obesity and cardiometabolic risk outcomes requires further study. Methods. Adult data from the National Health and Examination Survey (NHANES Continuous 1999–2016, n = 12,636 to 32,012) with data for blood or urinary metals concentrations and body mass index were used. The study aim was twofold: (1) to determine the association between heavy metals and obesity and (2) to examine the influence of heavy metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Previous literature in drinking water suggested high-Ba communities had lower cardiovascular disease and total mortality [43,44], which was similar to our results. Additionally, this study showed a signi cant interaction effect on blood pressure between urine Ba and overweight and obesity among children, which was consistent with Swayze et al study [45]. The study included 12256 participants from the continuous National Health and Nutrition Examination Survey 1999-2016 and suggested a greater effect of barium on hypertension in those with obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Previous literature in drinking water suggested high-Ba communities had lower cardiovascular disease and total mortality [43,44], which was similar to our results. Additionally, this study showed a signi cant interaction effect on blood pressure between urine Ba and overweight and obesity among children, which was consistent with Swayze et al study [45]. The study included 12256 participants from the continuous National Health and Nutrition Examination Survey 1999-2016 and suggested a greater effect of barium on hypertension in those with obesity.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies describing the involvement of trace elements and heavy metals in the development of dyslipidemia factors, we found a negative correlation between various blood cholesterol fractions (e.g., TC, LDL-C) and plasmatic minerals (e.g., iron, cobalt, chromium, arsenic, lead). This could be attributed to the essential roles that trace elements seem to play in ameliorating atherogenic dyslipidemia through a myriad of mechanisms (e.g., lipid β-oxidation, expression of peroxisome proliferator-activated receptors), and particularly by interfering with cholesterol metabolism (37)(38)(39). Surprisingly, a positive association was found between plasma TG, iron, zinc, and lead, which could be due to their dietary co-occurrence (e.g., animalbased products).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly negative interaction between blood Pb and BMI (only that of obesity but not overweight) was found. Conversely, Swayze et al ( 54 ) found an interaction between high Pb levels and non-obese subjects (BMI < 30 kg/m 2 ). This may be due to inconsistent results due to different definitions of obesity.…”
Section: Discussionmentioning
confidence: 93%